Coding 101 (Out of Print) - Davoren Ann Chick (Association of American Medical Colleges, 2013)
Abstract Coding 101 is a modular, self-study curriculum addressing knowledge necessary to code and bill for physician-provided services. Coding 101 was designed for internal medicine residents, but is suitable for all clinical learners from advanced medical students through faculty. The curriculum is designed to allow adult learners to independently engage with the learning components at their own pace. A learner's guide is provided to assist independent study, and a teacher's guide is provided for residency faculty who wish to use Coding 101 as a springboard for program implementation. A summative exam is provided to allow portfolio documentation of minimum knowledge achievement. A previous limited version of Coding 101, comprising only 3 videos with limited suggested online links, was Accepted with Acclamation in 2007 as MedEdPORTAL #436. The current version of Coding 101 has been extensively rewritten, reformatted, and expanded; it now includes 8 video modules, formative quizzes, case study examples, a summative examination, and expanded supplementary resources. The audiovisual modules are provided as individual mp4 videos. Formative quizzes are provided in interactive PowerPoint format. A summative examination is provided in a document that faculty can implement on their own tracking systems; access to an online version (not MedEdPORTAL peer reviewed) is provided via reference URL in the Instructor's Guide. This content has been successfully implemented by numerous internal medicine residency programs. At the University of Michigan, the content is provided to learners for optional review and self-study, and is well-received by learners. Due to benefit perceived by the central billing office, the University of Michigan Health System now uses the site for orientation of new faculty as well as residents. Feedback from national users of Coding 101 has been highly positive. In 2010, the Association of Program Directors in Internal Medicine E-Learning Task Force endorsed the curriculum as a highly rated educational site. The American College of Physicians (ACP) has selected Coding 101 as a resource for the ACP Center for Practice Improvement and Innovation website, under "Running a Practice/Payment and Coding/Coding". Institutions ranging from commercial coding audit companies to VA hospitals to university training programs are active users of Coding 101 for training of their employees and learners. Most residency programs find it easiest to simply make the content available and encourage application of the content in clinical learning settings. Residents have demonstrated self-motivation to review the content when it is made available, because it relates to future payment. Programs who wish to document minimal knowledge achievement require successful completion of the provided summative knowledge examination.